2019
DOI: 10.1029/2018wr024357
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning for Prediction of Saturated Hydraulic Conductivity and Its Sensitivity to Soil Structural Perturbations

Abstract: Saturated hydraulic conductivity (Ks) is a fundamental soil property that regulates the fate of water in soils. Its measurement, however, is cumbersome and instead pedotransfer functions (PTFs) are routinely used to estimate it. Despite much progress over the years, the performance of current generic PTFs estimating Ks remains poor. Using machine learning, high‐performance computing, and a large database of over 18,000 soils, we developed new PTFs to predict Ks. We compared the performances of four machine lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 97 publications
(113 reference statements)
3
85
0
Order By: Relevance
“…When the methods are homogeneous, the RMSE value is usually around 0.6-0.7 log 10 (cm day -1 ) (Zhang and Schaap, 2017). Araya and Ghezzehei (2019) report that the PTF with the highest accuracy in the literature has and RMSE of 0.3-0.4 log 10 (cm day -1 ). In Lilly et al (2008), the performance of the KS predictions and findings were similar to this study.…”
Section: Saturated Hydraulic Conductivitymentioning
confidence: 97%
See 1 more Smart Citation
“…When the methods are homogeneous, the RMSE value is usually around 0.6-0.7 log 10 (cm day -1 ) (Zhang and Schaap, 2017). Araya and Ghezzehei (2019) report that the PTF with the highest accuracy in the literature has and RMSE of 0.3-0.4 log 10 (cm day -1 ). In Lilly et al (2008), the performance of the KS predictions and findings were similar to this study.…”
Section: Saturated Hydraulic Conductivitymentioning
confidence: 97%
“…Machine learning methods can be more robust to construct PTFs in comparison to previous approaches such as linear regression or simple decision trees if relationship between the predictors and response is highly non-linear (Araya and Ghezzehei, 2019). The random forest algorithm (Breiman, 2001) is able to outperform other machine learning methods (Olson et al, 2018), which was also shown for predicting soil properties (Hengl et al, 2018;Nussbaum et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When the methods are homogeneous, the RMSE value is usually around 0.6-0.7 log10 (cm day -1 ) (Zhang and Schaap, 2017). Araya and Ghezzehei (2019) report that the PTF with the highest accuracy in the literature has and RMSE of 0.3-0.4 log10 (cm day -1 ). In Lilly et al (2008), the performance of the KS predictions and findings were similar to this study.…”
Section: Saturated Hydraulic Conductivitymentioning
confidence: 97%
“…The global dataset in SWIG may allow for such a wide variety of soil conditions for the same land use category that the value of land use alone as a predictor becomes less significant. The infiltration rate should be affected by the initial water content in the soil, the water content of which was an important variable for predicting hydraulic conductivity (Araya and Ghezzehei, 2019). Since the initial soil water content is only available in 31% of the infiltration data in the SWIG database, initial soil water content was not included in this study.…”
Section: Equationmentioning
confidence: 99%